Robert Frost - Frost, Robert, 1874-1963.; Schmidt, Gary D.; Sorenson, Henri (New York : Sterling, 1994)
A collection of poems about the four seasons by one of best-known American poets.
Includes index.
10 11 13 15 17 19 23 27 29 31 35 39
Keywords: Children's poetry, American; American poetry